INTERAKSI PENGGUNAAN PUPUK KANDANG TERHADAP PERTUMBUHAN BIBIT PORANG - Suyani, Ida Sugeng; Arifin, Zainol; Hasanah, Imroatul; Hartanti, Aprilia; Su"ud, Mochamad (BUANA SAINS, 2024)
The purpose of this study was to ascertain how different types of manure and bulbil size affected the growth of porang seedlings. This study used a Randomized Block Design with two factorials, namely, treatment of manure (P) with four kinds, namely chicken manure, cow manure, and goat manure The second factor is the size of bulbil with three types of size such as small (2 - 3,25 gr), medium (6 - 6,85 gr) and big (9 - 9,32 gr). The parameters observed in this study were plant height (cm), stem diameter (cm), leaf width (cm), number of leaves (strands), and percentage of finished seedlings. The results showed that Bulb weight 9 gr – 9.32 gr gives the best average in the plant height, number of leaves, leaf area, number of roots, and percentage of finished seedlings. Goat manure gives the best average for plant height, leaf area, and number of roots. There was an interaction between bulbil weight and type of manure on parameters of plant height.